An Existence Result for a Generalized Quasilinear Schrödinger Equation with Nonlocal Term - Quanqing Li; Kaimin Teng; Jian Zhang; Jianjun Nie (Journal of Function Spaces, 2020)
In this paper, we consider the following generalized quasilinear Schrödinger equation with nonlocal term −divg2u∇u+gug′u∇u2+Vxu=λx−μ∗upup−2u,x∈ℝN, where N≥3, g:ℝ→ℝ+ is a C1 even function, g0=1, g′s≥0 is for all s≥0, lim∣s∣→+∞gs/sα−1≔β>0 is for some α>1, and α−1gs≥g′ss is for all s≥0, 2α≤p≤2αN−μ/N−2, and 0<μ<N. We prove that the equation admits a solution by using a constrained minimization argument.